A possible role for immunogenetic factors in myositis developing after vaccination in the pre-covid-19 era - Alhassan, Eaman; Patnaik, Anna; Shamim, Ejaz A.; Pandey, Janardan P.; Rider, Lisa G.; Miller, Frederick W. (Frontiers in Immunology, 2025)
IntroductionVaccinations have had a transformative impact on public health, reducing the incidence of many infectious diseases and increasing survival. However, there remains uncertainty about the potential of vaccines to trigger autoimmune diseases such as the idiopathic inflammatory myopathies (IIM). Myositis after vaccination (MAV) is a rare clinical entity, but given immunogenetic associations with other adverse events, we explored genetic risk factors, particularly human leukocyte antigen (HLA) alleles and GM/KM immunoglobulin allotypes, that may predispose individuals to develop MAV.MethodsWe examined clinical characteristics, vaccination history, autoantibodies, HLA alleles and GM/KM allotypes from 56 patients who developed MAV, 133 myositis cases with no documented vaccination within 6 months of onset (non-MAV), and 527 healthy controls from the pre-COVID-19 era. Genotyping for HLA and GM/KM allotypes was performed by standard assays. Differences in allele frequencies in race-matched groups were evaluated using chi-square tests, odds ratios (OR) and 95% confidence intervals (CI). Multivariate logistic regression adjusted for age, sex, and vaccination type. Statistical significance was defined as a Holms corrected p-value of less than 0.05.ResultsNo clinical or serologic differences were found between MAV and non-MAV patients. However, the HLA-DQA1*03:03 allele was a unique risk factor for MAV in Caucasians (OR=3.87, 95% CI=1.56-9.54, p=0.002), while the known myositis risk factor, HLA-DRB1*03:01, was a protective factor for MAV (OR=0.41, 95% CI=0,18-0.94, p= 0.033). GM2, GM13, and KM1 allotypes were more frequently observed in MAV patients than healthy controls, and other HLA alleles were risk or protective factors for specific vaccines given in patients who developed MAV.ConclusionImmunogenetic factors may influence the likelihood of developing MAV. Further studies of larger, deeply phenotyped populations are needed to confirm these associations and could inform personalized risk assessments and targeted interventions, thereby enhancing vaccine safety.